„Denglish” The Fusion of German and English - Safina Farida Axatovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The development of language is a fascinating study. The linguistic phenomenon known as "Denglish" represents a unique blend of German and English, reflecting the cultural and linguistic interplay in our globalized world. As English continues to assert itself as the lingua franca of international communication, Denglish has emerged as a testament to the interconnectedness of languages and cultures. In my article explains how Denglish has become increasingly prevalent in today's globalized world and explores its historical origins.